Coordinating development: Can income-based incentive schemes eliminate pareto inferior equilibria? - Philip Bond; Rohini Pande (Yale University, Economic Growth Center, 2005)
Individuals' inability to coordinate investment may significantly constrain economic development. In this paper we study a simple investment game characterized by multiple equilibria and ask whether an income-based incentive scheme can uniquely implement the high investment outcome. A general property of this game is the presence of a crossover investment point at which an individual's incomes from investment and non-investment are equal. We show that arbitrarily small errors in the government's knowledge of this crossover point can prevent unique implementation of the high investment outcome. We conclude that informational requirements are likely to severely limit a government's ability to use income-based incentive schemes as a coordination device.
Keywords: O21; H23; 330; Coordination; public policy; income taxation; implementation